STANDAR MUTU PENDIDIKAN BERBASIS KOMPETENSI: KAJIAN TEORITIS DAN IMPLIKASI PADA KURIKULUM SERTA EVALUASI PEMBELAJARAN - ASMIATI; SIMINTO; MUSYARAFAH (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Competency-Based Education (CBE) has become the dominant paradigm in the reform of global education systems since the late twentieth century. This article aims to theoretically examine the concept of competency-based educational quality standards and analyze their implications for curriculum development and learning evaluation systems. Using a systematic literature review approach on 20 recent reference sources, this study finds that: (1) CBE quality standards encompass integrated dimensions of knowledge, skills, and attitudes within measurable learning outcomes frameworks; (2) the curricular implications of CBE require a shift from content-centered to learner-centered curriculum design; and (3) competency-based evaluation systems necessitate the use of authentic assessment, portfolios, and comprehensive performance-based assessments. This article concludes that the effective implementation of CBE requires alignment among quality standards, curriculum design, and evaluation instruments, as well as continuous support for educators’ capacity development.